Circulating differential miRNAs profiling and expression in hexavalent chromium exposed electroplating workers. (December 2020) - Jia, Junlin; Li, Tao; Yao, Chunji; Chen, Junfei; Feng, Lingfang; Jiang, Zhaoqiang; Shi, Li; Liu, Jiaqi; Chen, Junqiang; Lou, Jianlin
Abstract: Hexavalent chromium [Cr (Ⅵ)] has extensive applications in industries, and long-term occupational exposure to Cr (Ⅵ) may lead to lung carcinoma and other cancers. While microRNA (miRNA) can take part in carcinogenesis, little is known about its expression profile in the population with Cr (Ⅵ) exposure. Thus, this study aimed to explore miRNA expression profiles in Cr (Ⅵ) exposed workers and to identify the potential biological function of differentially expressed miRNAs. A total of 45 significant differentially expressed miRNAs were identified by the miRNA array. The results of validation showed that miR-19a-3p, miR-19b-3p, and miR-142-3p were downregulated and miR-590-3p and miR-941 were upregulated in the exposure group. Multivariate analysis demonstrated that age, exposure duration and urinary chromium level were associated with one or more miRNAs expression. Target gene analysis indicated that these miRNAs might participate in the regulation of DNA damage-related signaling pathways. Taken together, Cr (Ⅵ) exposure can result in differential expression of miRNAs in occupational workers, and the expression of these miRNAs is correlated with the level and duration of Cr (Ⅵ) exposure, and the differentially expressed miRNAs may participate in DNA damage response. Graphical abstract: Image 1 Highlights: Hexavalent chromium exposure can result in differential expression of miRNAs. Exposure duration and urinary Cr level were associated with miRNAs expression. The differentially expressed miRNAs may play a role in DNA damage response.